Marketing Cooperatives and sustainable Agricultural development in Rulindo District, Rwanda - Nkubito, Habyarimana Jean Pierre (Kabale University, 2020)
The study examined the contribution of marketing cooperatives in sustaining the development of agriculture in Rulindo district of Rwanda. The objectives of the study were; to identify activities and services of marketing cooperatives – driven agriculture that are leading to sustainable agricultural development in Rulindo district, to analyse the perceptions of marketing cooperatives members toward agricultural marketing cooperatives activities and services improvement in Rulindo district, to examine the contribution of marketing cooperatives to the socio-economic development and environmental management by rural farmers in Rulindo district, to identify challenges to the development of marketing cooperatives-driven Agriculture, in Rulindo district. The literature was reviewed in lines with objectives. The methodology used in this study included, descriptive survey design with qualitative and quantitative data collection approaches, questionnaire and sampling. The data was collected from a sample population of 95 members randomly selected from thirteen marketing cooperatives –driven agriculture; one Agro dealers marketing cooperatives, five Crops production and marketing cooperatives, five Livestock production and marketing cooperatives, one Crops and livestock production and marketing cooperatives and one Environment conservation and management marketing cooperatives. Randomly selected agricultural marketing cooperatives are located in five district zones; North, South, Central, West and East and in the respective five sectors; Cyungo, Shyorongi, Mbogo, Burega, and Bushoki; each sector in each district zone. The findings revealed that the agricultural marketing cooperatives addressed in the study made considerable socio-economic and environmental contribution to the sustainability of agricultural development and to the well being of their members. Members felt optimistic that marketing cooperatives activities and services brought some sort of improvement in the sustainability of agricultural development and in the living condition of the people in their community and wish the marketing cooperatives activities and services to expand. Challenges encountered by agricultural marketing cooperatives towards sustaining the development of agriculture in Rulindo district were identified and categorized into five sections; organizational or internal, external, infrastructural, natural and socio-cultural and economic challenges. The most important of them were: limited Capacity on management of agricultural marketing cooperatives, inadequate initial capital, lack of transparency and accountability, low price of farm produces, high cost of production, low linkage with financial institution, small and fragmented farm holdings, lack of market structure, lack of storage and transportation facility, lack of access, usage and ownership of ICTs, climate change, inappropriate distribution of agricultural assets and population pressure on land resources. The study recommends that collective savings action is encouraged because it strengthens members’ market position, bargaining power, lobbying power, meeting their household consumption needs and enhancing potential income generating capacity together with investing on own education and health care requirements.